Global Challenges as Factors Empowering the Global Competences of Heads of Educational Institutions - Bilbokaitė-Skiauterienė, Ieva; Bilbokaitė, Renata (Acta Paedagogica Vilnensia, 2025)
Changes taking place in the world, such as, i.e. pandemics, immigration, the geopolitical situation, global inclusive education, ecology, in context, and global competencies, which include understanding of the broad context and worldview, communication-based on understanding and respect, ensuring the common well-being, are a set of interdisciplinary and intercultural values and actions based on them, which help to create a successful educational system. The study aims to analyze the factors of global challenges that condition the empowerment of the global competencies of heads of educational institutions. A qualitative approach was chosen for the research - a survey with open questions to reveal diverse viewpoints. Thirty-five heads of educational institutions participated in the study. Latent content analysis was used to analyze the research data. The study results showed that global competence, in the context of the pandemic, was developed by creating networking and cooperation, implementing solutions for transferring education to virtual spaces, promoting the active involvement of students in the educational process, and implementing educational goals. The immigration challenge caused the need for global competencies of education managers in managing the integration and education processes: the institutions faced the language barrier of the interested parties and the lack of interculturality. The global understanding of school leaders, based on the experience of foreign educational institutions, using various measures, is one of the solutions to the global immigration challenge. The challenge of ecological problems encourages the expression of global competencies of school leaders because the lack of infrastructure in educational organizations is experienced - sustainability is achieved through the purposeful use of resources, conservation, and the realization of various ideas in the educational process. School leaders develop global competencies to overcome the challenge of equality and inclusion through project and international activities and cooperation, considering examples of good practice and diversity of opinions.